Evaluation of artificial diets formulations for laboratory-based rearing spodoptera frugiperda - Dita Megasari; Dita Atasa; Denia Rista Damayanti; Arman Adrian Maulana; Aliyatul Najiyah; Syaiful Khoiri (Universitas Trunojoyo Madura, 2025)
Corn is an important food commodity that susceptible to pest attacks such as armyworm (Spodoptera frugiperda). This invasive pest attacks the growing points of corn plants and causes decreased productivity. Supporting biological research on this pest, the development of artificial feed is crucial considering the limited natural feed. This study aimed to evaluate the effect of artificial diet formulations on the preferences of S. frugiperda larvae. Three formulations with different compositions are studied in this research. Instar 3 larvae were subjected to a preference test to determine the rapid response of the larvae and the weight of the feed consumed (daily consumption). The preference test was carried out in duration 1, 2, 4, 6, and 24 hours. The results showed that Formula 3, which uses natural ingredients such as baby corn and corn sprouts, has the highest initial attractiveness (30% in 1 hour). The physical and chemical characteristics of artificial diet affect the preferences of larvae with formula 3 being the most effective for rapid response, and formulas 1 and 2 being more stable for continuous use. The highest daily consumption of larvae was in formula 3 (0.066 ± 0.027 grams). However, it was not significantly different from formula 1 (0.058 ± 0.029 grams). The use of artificial feeds in the laboratory rearing of S. frugiperda offers a viable alternative to natural feeds, with Formula 3 showing a high initial preference, Formula 1 remaining attractive over time, and Formula 2 showing lower consumption, likely due to its efficient nutritional composition, as evidenced by feeding activity through visible bite marks and feed perforations.